Conference of the Institute of Economic Research of the Slovak Academy of Sciences and the Economics and Management Institute of the University of Economic in Bratislava - Gonda, Vladimír
Informácia o zámeroch a cieľoch konferencie, ktorá sa konala 27. novembra 2016 na pôde Ekonomickej univerzity v Bratislave